Estimation and Assessment of Ionospheric Slant Total Electron Content (STEC) Using Dual-frequency NavIC Satellite System - Bhardwaj, Sharat Chandra; Vidyarthi, Anurag; Jassal, B. S.; Shukla, Ashish K. (Journal of Graphic Era University, 2021)
Many atmospheric errors affect the positional accuracy of a satellite-based navigation device, such as troposphere, ionosphere, multipath, and so on, but the ionosphere is the most significant contributor to positional error. Since the ionosphere’s dynamics are highly complex, especially in low latitude and equatorial regions, a dual-frequency approach for calculating slant total electron content (STEC) for ionospheric delay estimation performs better in these conditions. However, the STEC is ambiguous and it cannot be used directly for ionospheric delay prediction, accurate positioning purposes, or ionospheric study. As a result, STEC estimation and pre-processing are required steps prior to any positioning application. There is very little litera- ture available for STEC pre-processing in the NavIC system, necessitating an in-depth discussion. This paper focuses on how to extract navigational data from a raw binary file obtained from the Indian NavIC satellites, estimate and pre-process STEC, and build a database for STEC. It has been found that an hourly averaged STEC data is suitable for ionospheric studies and monthly mean value can be used for ionospheric behavioral research. Furthermore, the STEC is affected by diurnal solar activity, thus, the seven-month data analysis that includes summer and winter months has been used to study ionosphere action during the summer and winter months. It has been observed that STEC values are higher during the summer months than the winter months; some seasonal characteristics are also been found.